Purchasing Decisions in the Food Service Industry: Factors of Influence: Faktor-Faktor yang Mempengaruhi Keputusan Pembelian di Industri Layanan Makanan - Denta Scotania Balqis; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the impact of location, food quality, service quality, and price on purchasing decisions in the food service industry. A total of 96 respondents from customers of a specific food establishment were included in the sample. Quantitative methods were employed, and data were collected through questionnaires. The analysis involved validity and reliability tests, as well as tests for normality, multicollinearity, heteroscedasticity, linearity, and autocorrelation. Multiple linear regression analysis, T tests, and multiple correlation coefficient (R) were conducted, along with the determination coefficient (R2). The findings demonstrated that location, food quality, service quality, and price significantly influenced purchasing decisions at the examined food establishment. The implications of this research contribute to a deeper understanding of consumer behavior in the food service industry, enabling practitioners to enhance their strategies and improve customer satisfaction. Highlights: Quantitative study: This research utilizes a rigorous quantitative approach to examine the factors influencing purchasing decisions in the food service industry, providing robust empirical evidence. Influential factors: The study identifies and analyzes various factors, such as location, food quality, service quality, and price, that significantly impact customers' purchasing decisions in the food service industry. Customer satisfaction: Understanding the influential factors can help food service establishments improve their strategies, enhance customer satisfaction, and ultimately drive business success. Keywords: Purchasing decisions, Food service industry, Influential factors, Quantitative study, Customer satisfaction